PM.99 Syphilis Serology in Pregnant Women Over a Period of 7 Years (2005–2011) in a Large Maternity Hospital in Dublin, Ireland. (26th April 2013) - Varughese, A; Jackson, V; Cafferkey, M; Brennan, M; Lawless, M; Ciprike, V; Eogan, M; Ferguson, W; Coulter-Smith, S; Lambert, J
Abstract : Nearly 1.5 million pregnant women are infected with probable active syphilis each year, and approximately half of infected pregnant women who are untreated, will experience adverse outcomes due to syphilis, such as early fetal loss and stillbirth, neonatal death, low-birth-weight infants, and infants with clinical evidence of infection. Data for all patients with positive treponemal serology at booking visit from 2005 to 2011 was gathered. Between 2005 and 2011, 179/64349 women had positive syphilis serology representing 0.28% of the patient population. These women were between the age of 19 and 41 with a higher prevalence among women of East European origin. In the 7 year period, 1 case of congenital syphilis was recorded. This patient was a DCDA twin pregnancy who booked late at 22 weeks and delivered prematurely at 23 weeks. Hence, syphilis treatment was not commenced. This study highlights the continued prevalence of positive syphilis serology in our pregnant population. Our combined obstetric and infectious disease clinic optimises opportunities for appropriate treatment and follow-up. Contact tracing and screening for other sexually transmitted infections are also vital components of this service. In the current economic climate, with continued emphasis on provision of cost-effective healthcare it is important to justify the cost of screening 67921 women to identify 179 cases. Untreated syphilis has a range of antenatal and paediatricsequelae and thus we recommend that screening for syphilis continues, particularly considering frequent migration of women from Eastern Europe to this country.